Efficiency of Manual Scanning in Recovering Rare Cellular Events Identified by Fluorescence In Situ Hybridization: Simulation of the Detection of Fetal Cells in Maternal Blood. (8th March 2012) - Emad, Ahmed; Ayub, Seemi; Samassékou, Oumar; Grégoire, Marie-Chantal; Gadji, Macoura; Ntwari, Aimé; Lamoureux, Josée; Hemmings, Francis; Tafas, Triantafyllos; Kilpatrick, Michael W.; Krabchi, Kada; Drouin, Régen
Abstract : Fluorescence in situ hybridization (FISH) and manual scanning is a widely used strategy for retrieving rare cellular events such as fetal cells in maternal blood. In order to determine the efficiency of these techniques in detection of rare cells, slides of XX cells with predefined numbers (1–10) of XY cells were prepared. Following FISH hybridization, the slides were scanned blindly for the presence of XY cells by different observers. The average detection efficiency was 84% (125/148). Evaluation of probe hybridization in the missed events showed that 9% (2/23) were not hybridized, 17% (4/23) were poorly hybridized, while the hybridization was adequate for the remaining 74% (17/23). In conclusion, manual scanning is a relatively efficient method to recover rare cellular events, but about 16% of the events are missed; therefore, the number of fetal cells per unit volume of maternal blood has probably been underestimated when using manual scanning.